Hazard Analysis and Critical Control Points in Cocoa Bean Fermentation - Muh. Ruslan Yunus (Hasanuddin University, 2016)
The objective of this research is to develop Hazard Analysis and Critical Control Points (HACCP) in cocoa bean fermentation at farmer level, starting from harvesting of cocoa pods until storage of dried fermented cocoa beans. The case study was conducted at Fajar Mas and Mandar Jaya cocoa farmer groups, located in Bukit Sutera Village, District of Larompong, Luwu Regency of South Sulawesi Province, Indonesia. For quality and food safety assurance, production process follows standard operation procedures, though in general the process is done by manual means. Of 11 steps of the process, sortation of cocoa pods, sortation of wet- cocoa beans, and drying of cocoa beans have been identified as CCPs. Potential hazards are found as biological hazards i.e. molds, especially Aspergillus spp., insects, Salmonella, E. coli and pest, and physical hazards i.e. waste and foreign matters. Verification of the HACCP showed compliance with SNI 2323-2008 for moisture, germinated, moldy, and insect damaged bean, insect, foreign matter, waste, and slaty bean contents. Implementation of the HACCP principles by the cocoa farmer groups in producing dried- fermented cocoa beans consistently will improve quality and food safety of the product, which will increase their bargaining power in the cocoa market.